Niat Investor di Bali Dalam Memilih Saham di Masa Pandemi Covid-19 - Komang Fridagustina Adnantara (Juara: Jurnal Riset Akuntansi, 2021)
The COVID-19 pandemic has made Bali's economy slump. However, the growth of stock investors in Bali increased by 76.14 percent at the end of 2020, and the value of share ownership in Bali grew by 74.78 percent. This study aims to determine the effect of Subjective Norms, Perceived Behavioral Control, Quality of Accounting Information, and Unsystematic Risk Perception on the Investor Intention in Bali to choose stocks during the Covid-19 pandemic. The dependent variable in this study is the intention of investor in stock selection, while the independent variables consist of Subjective Norms, Perceived Behavioral Control, Quality of Accounting Information, and Unsystematic Risk Perception. The respondents in this study was consisted of 199 individual investors. The sampling technique was done by convenience sampling technique, and the data was analyzed by using multiple linear regression analysis method. The test results show that the Subjective Norm and Quality of Accounting Information have a significant effect on Investor Intentions in Stock Selection. Meanwhile, The Perceived Behavioral Control and Unsystematic Risk Perception does not have significant effect on Investor Intention in Stock Selection.